C24 TWIDDLER SYNDROME AND HEART FAILURE: INTEGRATION OF REMOTE MONITORING AND CARDIOLOGY TELECONSULTATION FOR OPTIMAL MANAGEMENT. (18th May 2022) - Gatto, M; Dominici, T; Rinaldi, M; Rinaldi, D; Percoco, F; Tung, M; Pontiroli, C; Persi, A; Ciccaglioni, L; Kol, A
Abstract: The prevalence of heart failure in the population and the COVID pandemic have rendered increasingly necessary the integration of remote monitoring with cardiology teleconsultation. A patient with dilated cardimiopathy was subjected to ICD implantation (Boston Scientific Perciva DR) with remote monitoring (LatitudeTM). One month after implant, remote monitoring recorded an increase in the HeartLogicTM heart failure index, a decrease of right ventricular and atrial sensing, contextually to fluctuations of the impedance values of the two leads (Fig. 1 ). The patient reported having performed shoulder's rehabilitation therapy with probable manipulation of the ICD pocket. Chest X–ray showed dislocation of both leads with distal end of right atrial catheter in superior vena cava and distal end of right ventricular catheter in right atrium (Fig. 2A ) and kinking of proximal segments (Fig. 2B ), a picture compatible with diagnosis of Twiddler's syndrome. Implant revision confirmed lead kinking in the subcutaneous pocket (Fig. 3A ). The atrial catheter, given the amount of tissue deposited at its distal end (Fig.3B ) which prevented its active fixation, was replaced. Following discharge, an increase in the HeartLogicTM Heart Failure Index was detected. The outpatient visit showed the presence of pleural effusion and medical therapy was therefore optimized. In order to avoid frequent ambulatory visits to the patient, a cardiology teleconsultation was planned, which enabled to verify the clinical benefit of therapy's variation. Remote device monitoring confirmed HeartLogicTM Heart Failure Index normalization. In conclusion, the integration of remote monitoring with cardiology teleconsultation, enables to timely detect device malfunctions and prevent episodes of heart failure, avoiding further hospitalizations. This integration is even more useful and necessary in geographically disadvantaged areas, strengthening the link between the territory and the hospital, improving patients compliance and therapeutic adherence and thus allowing a progressive improvement of the symptoms and quality of life of heart failure patients.